Occupational stress in teachers - Chandraiah, K. (New Delhi : A P H Publishing Corporation, 2010)
Study conducted among the private and public college teachers of Calcutta City in West Bengal, India.
Includes bibliography.
Keywords: College teachers -- Job stress -- India -- Kolkata; College teachers -- Job satisfaction -- India -- Kolkata; Locus of control -- India -- Kolkata